Pancasila in the Perception and Practice of Religious-Based University Students in Bandung - Sapsudin, Asep; Wibisono, Muhammad Yusuf (Hanifiya: Jurnal Studi Agama-Agama, 2024)
Pancasila is the ideological guideline of the Indonesian state. As a philosophical foundation, Pancasila is a guideline for civic behavior. Religious pluralism is a challenge that must be answered by Pancasila which is practiced in the lives of Indonesian society. As part of society who must participate in the development of state ideology, students are an important part in the practice of Pancasila. By taking samples from Theology students, this study compares how Pancasila is perceived both from a cognitive and practical perspective by Catholic students at Parahyangan Catholic University (UNPAR) and Islamic students at Sunan Gunung Djati State Islamic University (UIN). Both universities are in Bandung, which is a big city inhabited by followers of various religions. The study was carried out using a qualitative and descriptive approach to the students by observation, interviews and documentation studies from the two groups of theology students. The analysis is carried out using an interactive model, which consists of data interpretation, data classification, inference and data presentation activities. The advantage of this model is that it can be taken back from the field if something is still not perfect. The theoretical analysis is based on the theory of political participation and the theory of ideological perception and practice. The research results show that Indonesia's basic philosophical framework, developed differently among Islamic and Catholic students, shows the intersection between religious beliefs and national ideology. Islamic students often explore the complex relationship between Islamic principles and the secular nature of Pancasila. Although divinity is in line with Islamic monotheism, interpretations of the ideals of democracy and social justice within the Pancasila framework can vary. Some Islamic students participate actively in societal processes, contributing to democratic values, but there are differing discussions regarding the compatibility of certain Pancasila principles with Islamic teachings. On the other hand, Catholic students approach implementing Pancasila by emphasizing ethical and moral values that are in accordance with the teachings of their religion. Social justice, which is a core principle of Pancasila, is in line with Catholic doctrine, thereby encouraging Catholic students to get involved in initiatives that address social inequality. Both Islamic and Catholic students contribute to the implementation of Pancasila in their unique ways. However, they show that the principles of Pancasila can become a common foundation for religious communities in Indonesia. The variety of ways these students navigate its application reflects Pancasila's ability to accommodate diverse religious perspectives and contribute to Indonesia's collective identity. The political participation of students of different religions can have a significant impact on the development of the state ideology of Pancasila. Students feel it is important to understand and uphold the Pancasila ideology to become politically mature citizens and contribute to building a democratic political system. Efforts to curb the politicization of religion and encourage interfaith dialogue are very important to uphold the Pancasila ideology in Indonesia.